Total energy expenditure and ad Libitum Fluid/Nutrient intake during a 24-Hour Mountain-Bike event: a case study - Dodds, P.; Schoeller, D.; Shriver, T.; Ruby, B. (International Journal of Sports Physiology and Performance, 2023)
The measurement of total energy expenditure (TEE) outside of the laboratory enables a more comprehensive understanding of the human ceiling for extended work and competition. Doubly labeled water remains the gold standard for quantifying the extended (several hours to days) TEE for humans in free-living environments without the need for additional body-worn sensors or expired-air collection, thereby optimizing both accuracy and portability concerns.